2012
DOI: 10.1016/j.iimb.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

From wrongdoing to imprisonment: Test of a causal–moral model

Abstract: The authors tested a causalemoral model of punishment in which (a) causal attribution and moral responsibility are distinct precursors of punishment, and (b) dispositional attribution leads to blame which, in turn, determines imprisonment. Specifically, whereas severity of outcome impacts punishment directly, circumstances of the crime and the culture of the observers impact punishment through causal attribution and blame, respectively. In an experiment, Singaporeans and Americans read about a crime that (a) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In the absence of measures of punishment goals, therefore, the causal-moral model predicts a direct effect of severity of outcome on the imprisonment recommended for the offender. Supporting this prediction, Singh et al (2012) also found a main effect of severity of outcome on imprisonment for the offender but not on dispositional attribution or blame to him. Given this evidence, Models 1 and 2 of Figure 1 predict only a direct effect of severity of outcome on collective imprisonment.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…In the absence of measures of punishment goals, therefore, the causal-moral model predicts a direct effect of severity of outcome on the imprisonment recommended for the offender. Supporting this prediction, Singh et al (2012) also found a main effect of severity of outcome on imprisonment for the offender but not on dispositional attribution or blame to him. Given this evidence, Models 1 and 2 of Figure 1 predict only a direct effect of severity of outcome on collective imprisonment.…”
mentioning
confidence: 67%
“…Even when East Asians do not see an individual person as less causally involved in what he or she did, they are more willing than Westerners to extend blame to his or her group . Thus, the effect of culture on the collective imprisonment should be mediated by collective blame, not dispositional attribution (Singh et al, 2012).…”
mentioning
confidence: 97%
See 3 more Smart Citations